2012
DOI: 10.1254/jphs.11157fp
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Dose–Effects of Multi-glycoside of Tripterygium wilfordii HOOK. f. on Glomerular Inflammation and Hepatic Damage in Two Types of Anti-Thy1.1 Glomerulonephritis

Abstract: Abstract. Multi-glycoside, one of the extracted compounds from Tripterygium wilfordii HOOK. f. (GTW), has been shown to be clinically effective in suppressing glomerular inflammation in chronic kidney disease. However, its clinical application is often limited by its cytotoxic actions on the liver. This study was performed to contrast the dose-effects of GTW on glomerular inflammation and hepatic damage in two types of anti-Thy1.1 glomerulonephritis (GN). Rats with acute or chronic anti-Thy1.1 GN were either l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Currently, more than 200 compounds have been identified from the extracts of TwHF (Wan et al, 2012). Most of them show extensive pharmacological effects on anti-inflammation, immunosuppress, anti-tumor and anti-oxidant (Tao and Lipsky, 2000; Marks, 2011; Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 200 compounds have been identified from the extracts of TwHF (Wan et al, 2012). Most of them show extensive pharmacological effects on anti-inflammation, immunosuppress, anti-tumor and anti-oxidant (Tao and Lipsky, 2000; Marks, 2011; Lu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…35,36) Due to the merits of resource abundance and cheap price, TWHF has been widely used in glomerulonephritis and kidney transplantation. 11,[37][38][39] Triptolide is a major active ingredient of TWHF and has been shown to possess multiple biological activities. Triptolide was proved to be a potent inhibitor of vascular endothelial growth factor (VEGF) expression and production in endothelial cells, which could contribute to its anti-proteinuria effect in Thy1.1 glomerulonephritis and puromycin-induced nephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide was proved to be a potent inhibitor of vascular endothelial growth factor (VEGF) expression and production in endothelial cells, which could contribute to its anti-proteinuria effect in Thy1.1 glomerulonephritis and puromycin-induced nephrosis. 11,40,41) In cultured mouse podocytes, triptolide pretreatment suppressed reactive oxygen species generation and p38 mitogen-activated protein kinase activation while restoring RhoA signaling activity. 42) Our previous studies have confirmed that increased oxidative stress led to prominent tubule cell injury and podocyte damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical reports show that treatment combining traditional Chinese medicine (TCM) and western medicine leads to significant curative effects which are better than that of TCM or western medicine alone. T. wilfordii is a Chinese herbal extract which has anti-inflammation and immunologic suppression properties and is extensively applied to treat rheumatic disease, systemic lupus erythematosus, inflammatory bowel disease, nephritis, and many immune diseases (Wan et al, 2010;Wan et al, 2012;Chen et al, 2013). In this research, conventional treatment combined with orally-taken T. wilfordii tablets resulted in a distinct decrease of uTP and peripheral SCr, BUN, and TC with a significant increase in the ALB level, and the improvement was greater than that of conventional treatment.…”
Section: Discussionmentioning
confidence: 99%